2020
DOI: 10.7150/thno.45125
|View full text |Cite
|
Sign up to set email alerts
|

Targeting phosphatidylserine for Cancer therapy: prospects and challenges

Abstract: Cancer is a leading cause of mortality and morbidity worldwide. Despite major improvements in current therapeutic methods, ideal therapeutic strategies for improved tumor elimination are still lacking. Recently, immunotherapy has attracted much attention, and many immune-active agents have been approved for clinical use alone or in combination with other cancer drugs. However, some patients have a poor response to these agents. New agents and strategies are needed to overcome such deficiencies. Phosphatidylser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 192 publications
(186 reference statements)
1
58
0
Order By: Relevance
“…In this regard, it was recently shown that a chemical activator of p53 in combination with an antibody that targets PS on tumor blood vessels and disrupts tumor vasculature effectively inhibits metastasis of p53-expressing TNBC cells to the lungs in a mouse model (44). Our study further illustrated that PS should serve as a target for cancer therapy, as it is an essential component of the cancer cell membrane and plays an important role in maintaining cancer cell viability and metastasis (45)(46)(47).…”
Section: Discussionsupporting
confidence: 57%
“…In this regard, it was recently shown that a chemical activator of p53 in combination with an antibody that targets PS on tumor blood vessels and disrupts tumor vasculature effectively inhibits metastasis of p53-expressing TNBC cells to the lungs in a mouse model (44). Our study further illustrated that PS should serve as a target for cancer therapy, as it is an essential component of the cancer cell membrane and plays an important role in maintaining cancer cell viability and metastasis (45)(46)(47).…”
Section: Discussionsupporting
confidence: 57%
“…[12][13][14][15][16]23 The insights on how glycogen and lipids (cholesterol, phosphatidylserine, and stearic acid) can be linked to PR/ER and Ki67 molecular histotypes and how this relates to RT are reported by RS for the first time to our knowledge, although these metabolites have been studied intensively in the cancer research community. [56][57][58][59][63][64][65][66][67][68] The motivation to add extra chemicals such as leucine and valine into the reference chemical library was to potentially investigate whether RS and the GBR-NMF-RF framework could track changes in protein or amino acids in the breast cell lines. Proteins are difficult to trace because the amino acid composition of proteins can vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…The overall lipid composition of the cancer cell resembles that of normal cells, however, the asymmetric distribution of lipid classes between the inner and outer leaflets, normally found in eukaryotic cell membranes [745], is lost; they instead display a substantial concentration of phosphatidylserine in the outer leaflet. The selective disruption of lipid membranes rich in phosphatidylserine becomes a possible mode of action for cancer therapy: anticancer peptides [746,747] or drugs affecting the membranes of cancer cells [748].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%